1989
DOI: 10.1104/pp.90.1.185
|View full text |Cite
|
Sign up to set email alerts
|

Soluble and Bound Apoplastic Activity for Peroxidase, β-d-Glucosidase, Malate Dehydrogenase, and Nonspecific Arylesterase, in Barley (Hordeum vulgare L.) and Oat (Avena sativa L.) Primary Leaves

Abstract: An intercellular washing solution containing about 1% of the soluble protein, 0.3% or less of the glucose-6-phosphate dehydrogenase activity, but up to 20% of the peroxidase and 6-Dglucosidase activity of barley (Hordeum vulgare L.) or oat (Avena sativa L.) primary leaves was obtained by vacuum infiltrating peeled leaves with pH 6.9 buffered 200 millimolar NaCI. After this wash, segments were homogenized in buffer, centrifuged, and the supernatant was assayed for soluble cytoplasmic enzymes. The pellet was was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1
1

Year Published

1990
1990
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 28 publications
2
47
1
1
Order By: Relevance
“…In addition, increasing evidence suggests that proteins can be secreted into cell walls without having a signal peptide (Voigt and Frank, 2003;Slabas et al, 2004;Juarez-Diaz et al, 2006). Consistent with this model, 17 of the proteins were predicted to be so-called nonclassical secretory proteins (Bendtsen et al, 2004;Zhu et al, 2006), and among the 30 remaining proteins, 19 were previously identified in cell walls including two malate dehydrogenases, two glyoxalases I, three UDPGlc pyrophosphorylases, and 12 b-D-glucosidases (Gross, 1977;Fry, 1988;Li et al, 1989;Chivasa et al, 2002;Pitarch et al, 2002;Kleczkowski et al, 2004;Watson et al, 2004).…”
Section: Discussion Identification and Spatial Distribution Of Fractimentioning
confidence: 49%
“…In addition, increasing evidence suggests that proteins can be secreted into cell walls without having a signal peptide (Voigt and Frank, 2003;Slabas et al, 2004;Juarez-Diaz et al, 2006). Consistent with this model, 17 of the proteins were predicted to be so-called nonclassical secretory proteins (Bendtsen et al, 2004;Zhu et al, 2006), and among the 30 remaining proteins, 19 were previously identified in cell walls including two malate dehydrogenases, two glyoxalases I, three UDPGlc pyrophosphorylases, and 12 b-D-glucosidases (Gross, 1977;Fry, 1988;Li et al, 1989;Chivasa et al, 2002;Pitarch et al, 2002;Kleczkowski et al, 2004;Watson et al, 2004).…”
Section: Discussion Identification and Spatial Distribution Of Fractimentioning
confidence: 49%
“…The apoplast comprises xylem tracheids and vessels, cell walls, and intercellular spaces. Proteins extracted from the apoplast are soluble and/or loosely bound to cell walls or the outer surface of the plasma membrane (Li et al, 1989;Brune et al, 1994 Extraction of apoplastic proteins from CA leaves decreased immunologically detectable AFPs in total protein samples of the remaining leaf material (Fig. 3, D, F, and H), which indicates that most AFPs in winter rye are secreted proteins.…”
Section: Apoplastic Versus Intracellular Location Of Afpsmentioning
confidence: 99%
“…The apoplastic peroxidases are involved in the formation of cross-linkings within cell wall constituents. Some of them are bound to the cell wall, whereas others are soluble (7). These enzymes may also scavenge hydrogen peroxide in a way similar to that employed by vacuolar peroxidases, which first oxidize phenolics (14).…”
mentioning
confidence: 99%